Dysregulated immune cell responses in severe dengue pathogenesis - Yoo, Ji-Seung; Shporn, Oron Zvi; Sklan, Ella H. (Frontiers in Immunology, 2025)
Life-threatening severe dengue (SD) develops in a small subset of patients suffering from dengue fever (DF), a febrile disease that develops following infection with dengue virus (DENV). DENV is a mosquito-borne positive -sense RNA virus. The rapid spread of DENV vectors, which was exacerbated by climate change and inadequate control measures, has led to outbreaks affecting millions worldwide. There is no specific treatment for DF, and the recently introduced vaccines are ineffective in containing the current outbreaks. Like many other viral diseases, the immune system plays a key role in dengue pathogenesis. The lack of models replicating the disease’s immunopathological features has hampered the understanding of the immune system’s role in developing this disease. Recent advances, such as single-cell approaches, provide better systems and methodologies to study the role of different immune cells in SD, closing this gap and providing a better mechanistic understanding of disease pathogenesis and promoting the identification of targets for therapeutic interventions. Here, we summarize recent advances in SD research, focusing on immune cell interactions and their role in disease severity.